Trading up : the prospect of greater regulatory convergence in North America - Hart, Michael (CEPAL [S.l.]MX, 2007)
Examines the record of recent efforts to strengthen regulatory cooperation. Considers the degree and pace of cross-border and North American integration and explores the extent to which remaining regulatory impediments to integration can be addressed through intergovernmental cooperation strategies.